EFFORTS TO IMPROVE TEACHERS' COMPETENCE IN PREPARING LESSON PLAN DURING THE COVID-19 PANDEMIC THROUGH IN HOUSE TRAINING - Arpius (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This research was motivated by the government policies regarding the distance learning in which teachers played an important role to prepare effective learning for students. This research sought to improve teachers’ competence in preparing lesson plans by conducting in-house training activities. This research was conducted at SDN 014 Teratak Buluh with 9 teachers as the research subjects. The instrument was an observation sheet containing the information about the teachers’ competence in preparing lesson plans. The results showed that in cycle I the average score of the teachers’ competence was 67.22 with sufficient category. Then, the score increased in the second cycle to 78.33, which reached good category. Based on the results of this study, it can be concluded that the teachers’ competence in preparing the lesson plan during the Covid-19 pandemic increased through in-house training.